Community Radios as tools in non-formal education, subsidizing Environmental Education in peripheral urban regions - Hayashi, Carmino (2021)
The use of new information and communication technologies has enabled a great evolution in the teaching-learning processes, including in non-formal education. Among the various media, community radio stands out as a tool with great potential to reach a certain population, meeting its most specific and localized interests. The methodology in this study was based on bibliographic and documentary research, resulting in a wide and careful review of the literature on community radio as a strong means of intercommunication and non-formal environmental education, providing preventive knowledge and guidance in the preservation of the environment. Introductory aspects were analyzed and discussed in relation to educational ecosystems, involving the various media, with emphasis on the use of radio as an element of inter-relationship between inhabitants of a peripheral urban region. This review involved analysis and discussion in terms of concepts, history, legislation on community radio, as well as a non-formal educational tool in its contribution to the environmental education process. As a result of this study, it can be said that community radio stations contribute enormously to encouraging behavioural changes in relation to environmental education, sensitizing and guiding the formation of more informed, aware and, therefore, critical citizens who know how to fight for improvements and own well-being and that of the community, through sustainable local development.